Analysis of Hazardous and Toxic (B3) Management at the Puskesmas Sirnajaya - Setyaningtyas, Endah; Hartono, Budi (International Journal of Science and Society, 2024)
Management of Hazardous and Toxic Waste (B3) is a critical aspect in maintaining environmental health and safety, especially in health service facilities such as Community Health Centers. This research aims to analyze the B3 waste management system at the Puskesmas Sirnajaya, in order to identify the weaknesses and strengths of existing procedures and provide recommendations for improvements that can be implemented to increase the efficiency and safety of waste management. The research method used is a qualitative descriptive method with a case study approach. Data was obtained through direct observation, in-depth interviews with health workers and waste managers, as well as analysis of documents related to B3 waste management policies and procedures at the Puskesmas Sirnajaya. Data analysis was carried out thematically to identify patterns and main issues in B3 waste management. The research results show that the Puskesmas Sirnajaya, has B3 waste management procedures which include the stages of collection, temporary storage, transportation and handover to licensed third parties. However, there are several significant weaknesses, including a lack of routine training for officers, limited storage facilities that meet standards, and a lack of regular supervision and monitoring. Some of the advantages found were officers' awareness of the importance of B3 waste management and collaboration with third parties who have official certification.